2016
DOI: 10.1113/jp271936
|View full text |Cite
|
Sign up to set email alerts
|

Single cell transcriptome analysis of mouse carotid body glomus cells

Abstract: Key pointsr Carotid body (CB) glomus cells mediate acute oxygen sensing and the initiation of the hypoxic ventilatory response, yet the gene expression profile of these cells is not available.r We demonstrate that the single cell RNA-Seq method is a powerful tool for identifying highly expressed genes in CB glomus cells.r Our single cell RNA-Seq results characterized novel CB glomus cell genes, including members of the G protein-coupled receptor signalling pathway, ion channels and atypical mitochondrial elect… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
115
0
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 99 publications
(123 citation statements)
references
References 113 publications
7
115
0
1
Order By: Relevance
“…However, a study in 2016 did show evidence that β ionone is a functional ligand: this study demonstrated that cells natively expressing OR51E2 exhibited an increase in intracellular calcium in response to β ionone which was negated by transfection of siRNA for OR51E2 (27). In late 2015, it was reported that Olfr78 responded to lactate in addition to acetate and propionate(28), and this was confirmed by two other groups in 2016 (29, 30). Notably, microbial metabolism also contributes to circulating lactate levels.…”
Section: Short Chain Fatty Acid Receptorsmentioning
confidence: 77%
“…However, a study in 2016 did show evidence that β ionone is a functional ligand: this study demonstrated that cells natively expressing OR51E2 exhibited an increase in intracellular calcium in response to β ionone which was negated by transfection of siRNA for OR51E2 (27). In late 2015, it was reported that Olfr78 responded to lactate in addition to acetate and propionate(28), and this was confirmed by two other groups in 2016 (29, 30). Notably, microbial metabolism also contributes to circulating lactate levels.…”
Section: Short Chain Fatty Acid Receptorsmentioning
confidence: 77%
“…To determine the role of NSC in glomus cell excitability, we need to identify the gene that encodes NSC to delete or silence it. A recent single glomus cell transcriptome analysis indicated that TRPC3, TRPC5 and TRPM7 were most highly expressed TRP ion channels (Zhou et al, 2016). However, the single channel and pharmacological properties of these TRP channels do not match those of NSC, as most TRP ion channel have high single channel conductance (>40-pS) and the modulation by pharmacological agents such as 2-APB are clearly different (Kang et al, 2014).…”
Section: Discussionmentioning
confidence: 99%
“…normal) cytochrome a 3 , whereas the cytochrome a 3 incorporated in mitochondria of oxygen-sensing cells may have a low affinity for oxygen. Consistent with this hypothesis, recent investigations have demonstrated that NDUFA4L2 [52] and COX4I2 [53,54], two nuclear-encoded atypical subunits of the mitochondrial electron transport chain, are constitutively expressed in carotid body type I cells under normoxia [55]. This contrasts with a number of other cell types where NDUFA4L2 and COX4I2 expression is ordinarily low, but is increased during prolonged hypoxia [5254].…”
Section: A Pinch Of Ptolemy–ampk and The Carotid Bodymentioning
confidence: 95%
“…The effects on type I cells of hydrogen sulfide may not, therefore, be inconsistent with the conclusion drawn above. This perspective has recently received support from single-cell transcriptome analysis of mouse type I cells which identified few to no reads of the enzymes responsible for generating either carbon monoxide or hydrogen sulfide [55], respectively, haem oxygenase-2, or cystathionine-γ-lyase and cystathionine-β-synthase.As mentioned previously, conditional deletion in tyrosine hydroxylase-positive cells of Ndufs2 , a mitochondrial complex I gene which encodes a protein that participates in ubiquinone binding, has also been shown to selectively block carotid body activation during hypoxia (but not hypercapnia or hypoglycaemia) and thus the hypoxic ventilatory response [61]. The authors concluded that this probably results from loss, during hypoxia, of the capacity for signalling via increased generation of mitochondrial ROS.…”
Section: A Pinch Of Ptolemy–ampk and The Carotid Bodymentioning
confidence: 99%